ANALISIS PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI KOTA KENDARI - Sitti Rachma Ramadhani Maskur; Rostin Rostin; Asrianti Dja;wa (JEP (Jurnal Ekonomi Pembangunan), 2019)
This study aims to determine the effect of infrastructure development on economic growth in Kendari City. The data used in this study are secondary data in the form of time series data from 2003-2017 period consisting of constant price GRDP data, electricity infrastructure data and water infrastructure data in Kendari City. This study uses quantitative descriptive analysis and multiple linear regression. The software used is SPSS 22.0. The results of this study indicate that electricity infrastructure and water infrastructure have a significant influence on economic growth in Kendari City with a significant value of 0,000 <0.05. While Electricity Infrastructure partially has a positive and significant influence on economic growth significant value = 0.004 <0.05 and water infrastructure partially had a positive and significant effect on economic growth with a significant value = 0.001 <0.05. From the results of the study concluded that infrastructure development has a very important role in increasing and encouraging economic growth in a region, the development that occurs can have a good impact on the process of economic activity